2006
DOI: 10.1063/1.2245579
|View full text |Cite
|
Sign up to set email alerts
|

Core barrier formation near integer q surfaces in DIII-D

Abstract: Recent DIII-D experiments have significantly improved the understanding of internal transport barriers (ITBs) that are triggered close to the time when an integer value of the minimum in q is crossed. While this phenomenon has been observed on many tokamaks, the extensive transport and fluctuation diagnostics on DIII-D have permitted a detailed study of the generation mechanisms of q-triggered ITBs as pertaining to turbulence suppression dynamics, shear flows, and energetic particle modes. In these discharges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 25 publications
9
77
0
Order By: Relevance
“…This feature, identical to those observed in ref. [8,22], cannot be predicted by transport models since usually no role is given to rational surfaces. On the other hand rarefaction of rational flux surfaces, i.e.…”
Section: Ex/8-3mentioning
confidence: 99%
“…This feature, identical to those observed in ref. [8,22], cannot be predicted by transport models since usually no role is given to rational surfaces. On the other hand rarefaction of rational flux surfaces, i.e.…”
Section: Ex/8-3mentioning
confidence: 99%
“…After the realization that sufficiently large € E × B flow shear can substantially reduce the local turbulence and radial transport level [11], experiments have demonstrated that sheared flow indeed plays a crucial role in triggering edge and core barrier formation, and in maintaining turbulence suppression in the H-mode pedestal and in sustained internal barriers (for example, [7,8,[10][11][12][13][14][15][16][17]). With neutral beam injection and driven ion rotation in the radial momentum balance, or due to the ion pressure gradient, depending on the plasma regime, barrier evolution, and other experimental details.…”
mentioning
confidence: 99%
“…This has been attributed to stationary zonal flows (ZFs) near the rational surfaces (in particular the € q = 2 surface [8][9][10]). At higher heating power, the formation radius of transport barriers does not necessarily coincide with the location of rational magnetic surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present several possible mechanisms, like an ExB flow shear, a zonal flow, or a magnetic shear, have been proposed. One of these issues is the role of low-order magnetic surfaces in the formation transport barriers which have been discussed in a number of works [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%